The Roles of Individual Actors in Data-Driven Service Innovation – A Dynamic Capabilities Perspective to Explore its Microfoundations - Schymanietz, Martin; Jonas, Julia (Proceedings of the 53rd Hawaii International Conference on System Sciences, 2020)
The increasing amount of data that can be collected from interconnected devices offers various opportunities for the co-creative innovation of data-driven services. It demands for the integration of traditional and new actors that have to deal with alternating roles. Using a modified Delphi method, this study takes a microfoundational view and investigates the roles of individual actors that together shape an organization’s ability to innovate. By identifying relevant activities and their relative importance in the innovation of data-driven services, the study specifies nine actor roles and their contribution to organizational capabilities. The findings indicate that technical roles are less important than those that shape mindset and strategy. The paper contributes to current research on the utilization of data for service innovation by providing a microfoundational view of individual actors that helps to account for such higher-level phenomena as dynamic capabilitie
Keywords: Digital Services and The Digitalization of Services actors data-driven service innovation delphi dynamic capabilites